Pemerintahan Desa dalam Karakteristik Otonomi Desa di Sistem Negara Kesatuan Republik Indonesia - Wijayanto, Ronny; Dewi, Sri Anggraini Kusuma; Iswahyudi, Gesang (Fakultas Syariah INSURI Ponorogo, 2022)
Village autonomy is one of the urgencies for village government. This is in line with the reform mandate which emphasizes the spirit of regional autonomy. Village autonomy is expected to increase village independence. The legal issue in this research is the legal vacuum related to the regulation of village autonomy. This study aims to construct the idea of regional autonomy within the framework of the Unitary State of the Republic of Indonesia. This research is a juridical-normative research with three legal materials, namely primary legal materials including: the 1945 Constitution of the Republic of Indonesia, the Village Law, and the Regional Government Law. Secondary legal materials include books, websites, and journal articles related to legal issues. Non-legal materials include language dictionaries and legal dictionaries. The results of this study confirm that the idea of village autonomy in the Unitary State of the Republic of Indonesia must be positioned that village autonomy is